2013
DOI: 10.4137/ebo.s10539
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Evolutionary Patterns of the Insulin/FOXO Signaling Pathway

Abstract: The insulin/insulin growth factor-1(IGF1)/FOXO (IIF) signal transduction pathway plays a core role in the endocrine system. Although the components of this pathway have been well characterized, the evolutionary pattern remains poorly understood. Here, we perform a comprehensive analysis to study whether the differences of signaling transduction elements exist as well as to determine whether the genes are subject to equivalent evolutionary forces and how natural selection shapes the evolution pattern of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…However, no differentially expressed genes were associated directly with these pathways. This can possibly be attributed to their high degree of conservation [ 39 , 70 ], given that many of these genes are selectively constrained [ 71 , 72 ]. However, our analyses did reveal differential expression of genes involved in metabolism ( bgm , CG2469 , CG10116 , CG10962 , CG33958 , Cyp4d1 , GstD2 , HIP , Ipk1 , phr , SP1029 , tej , tld ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no differentially expressed genes were associated directly with these pathways. This can possibly be attributed to their high degree of conservation [ 39 , 70 ], given that many of these genes are selectively constrained [ 71 , 72 ]. However, our analyses did reveal differential expression of genes involved in metabolism ( bgm , CG2469 , CG10116 , CG10962 , CG33958 , Cyp4d1 , GstD2 , HIP , Ipk1 , phr , SP1029 , tej , tld ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings of elevated ωs agree with those of ref. 28 and supply further support that extracellular components are among the fastest evolving genes in the IIS/TOR network (22), as is likely true in other networks. Overall, our data are in agreement with reports that receptors and other extracellular components of signal transduction pathways appear to be under less purifying selection than intracellular components (51)(52)(53).…”
Section: Members Of Iis/tor Network Are Outliers In Evolutionary Ratementioning
confidence: 99%
“…S1) often experienced positive selection, whereas intracellular genes often experienced purifying selection (22)(23)(24)(25)(26)(27)(28), especially farther downstream in the intracellular network. These previous findings have supported the prediction that upstream extracellular factors (e.g., the initial components that interact with environmental stimuli in signal transduction pathways) may have larger impacts on signaling through the network than downstream components.…”
Section: Significancementioning
confidence: 99%
“…Studies have indicated that many factors affect the evolutionary rate of genes within gene pathways and networks. For example, gene position [ 3 , 4 ], protein length [ 5 ], the number of protein-protein interactions [ 6 , 7 ] and codon bias [ 8 , 9 ] have influence on gene evolution. Signaling pathways mediate the sensing and processing of both extracellular and intracellular stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with trends reported for the yeast HOG-signaling pathway [ 11 ] and the Caenorhabditis elegans and Drosophila insulin/TOR pathway [ 12 , 13 ]. In contrast, evolutionary patterns of the Insulin/FOXO signaling pathway across metazoan species genomes indicated that components within the middle of the pathway were rather under stronger purifying selection [ 9 ]. Moreover, within the Drosophila Ras signaling pathway, upstream genes have lower evolutionary rate, suggesting more constraints, than downstream genes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%